THE POSITION OF THE AL-QUR'AN AND HADITH AS A BASIS FOR EDUCATION - Awaliyah, Fuji; Arif, Mahmud (SYAHADAT: Journal of Islamic Studies, 2024)
The position of the Qur'an and Hadith is the main reference in the world of education. The Qur'an and Hadith have an important role as the basis of Islamic education. The existence of Islamic education as an effort of the people in a community institution that provides education. Not only that, sometimes education is also a source of effort in itself as a source of income in his life. Education can bring a good person and can interact in life by running as a social being constructively. The type of research used is literature study (library research). Data analysis is qualitative by sorting, searching, and finding to manage the data. The data sources used are primary data sources and secondary data. The primary data is from books, journals, about the position of the Qur'an to be studied in depth as a basis for this article. Secondary data, as complementary data used in journals, and articles that are relevant to the research conducted by the author. The results of this study indicate that the position of the Qur'an and hadith in Islamic education has similarities between the two, namely both are the main references in Islamic education, but both also have differences. Because if the Qur'an is a global revelation. So to understand it requires interpretation. While the position of the hadith plays an important role in providing a basis for strengthening and clarifying to answer the problems contained in the Qur'an. The concepts contained in the Qur'an, including education, are examples as role models.